Can the APACHE II score be used to assess the risk of mortality in the elderly with hip fractures? - Tarik Bujakovic; Samir Delibegovic (Medicinski glasnik, 2025)
Aim: Various predictive models have been developed to help identify patients with hip fractures with greater or lower probability of survival. The aim of this study was to establish the capacity of the APACHE II score to predict the survival of patients with hip fracture, in people aged over 65 years, and compare it with the existing score used to predict the survival of these patients. Methods: This was a prospective, cohort study conducted in a tertiary care teaching hospital including 410 consecutive patients with hip fracture aged ?65 years. As part of the preoperative preparation, general health of the patients was classified according to the ASA score. The Charlson Comorbidity Index (CCI), the Nottingham Hip Fracture Score (NHFS), the POSSUM-P and the APACHE II scores were analysed. Results: The sensitivity and specificity of the P-POSSUM score were 78.3 and 73.0, respectively, which was better than the APACHE II whose sensitivity and specificity were 56.6 and 89.7. The area beneath the ROC curve for P-POSSUM was 0.809, and for APACHE II, 0.803. However, there was no statistically significant difference between the APACHE II and P-POSSUM scores. The P-POSSUM and APACHE II scores were statistically significantly better than ASA, the Nottingham score and CCI. Conclusion: This study showed that POSSUM-P and APACHE II can be used to predict mortality in elderly people with hip fractures.
Keywords: ASA score; CCI; morbidity; older people; P-POSSUM score